2019
DOI: 10.1088/1361-6463/ab5b4f
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high resolution sensing of glucose concentration based on amplified half-integer localized surface plasmons mode

Abstract: Since the half-integer order localized surface plasmons mode is more sensitive to the change of the surrounding materials, an active spoof plasmonic microfluidic sensor using the mode for detecting minute change of glucose aqueous solutions has been proposed at microwave frequencies. By introducing an active coupling circuit near the slit of the spoof plasmonic resonator, the measured quality factor of the half integer order mode (n = 1.5) for the active spoof plasmonic resonator is increased from 148 to 40 00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The former sensors are smaller, can assess smaller sample volumes, have higher sensitivity than the latter, and do not require additional circuit parts. Moreover, conventional spoof SP-or LSP-based sensors have higher sensitivity to permittivity than sensors based on other methods because of the near-field enhancement [32][33][34][35]. 1 Measured value with only the sensor without any additional parts.…”
Section: Performance Comparison Of the Sensorsmentioning
confidence: 99%
“…The former sensors are smaller, can assess smaller sample volumes, have higher sensitivity than the latter, and do not require additional circuit parts. Moreover, conventional spoof SP-or LSP-based sensors have higher sensitivity to permittivity than sensors based on other methods because of the near-field enhancement [32][33][34][35]. 1 Measured value with only the sensor without any additional parts.…”
Section: Performance Comparison Of the Sensorsmentioning
confidence: 99%
“…It has been shown that the Q factor would decrease when the materials under test is high-loss, such as polar solutions [32]. To evaluate the sensitivity of the microwave plasmonic sensors, the figure of merit (FOM) is defined by FOM = Q × ∆f /∆ε, where Q is the quality factor, ∆f is the resonant frequency shift and ∆ε is the change of the relative dielectric constant [36]. Compared with other works in Refs.…”
Section: Experimental Verificationsmentioning
confidence: 99%
“…In the last few years, the idea of developing sensors based on microwave detection and microtechnology for biological characterization has been emerging [26]- [27]. The characteristic parameters of the fluids, even very small volumes (lower than few μL), can be accurately determined based on the measured impedance, resonant frequency, insertion loss, or the phase of the microwave or radio frequency (RF) signals [28]- [36], with the advantages of robustness, light weight and durability. However, the sensitivity is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic channels are commonly employed to control the inlet and outlet of the solution to build a more controllable environment. [40][41][42][43] Even though, resonance shifts have been reported to present reverse trends varying with the glucose concentration, when the detection limits approach the mg mL −1 level. [9,[44][45][46] These phenomena are inexplicable and indicate that there must be some issues to be addressed to lower any possible signal disturbances or null shifts.…”
Section: Introductionmentioning
confidence: 99%